The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5016/geociencias.v36i2.12593
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade Espacial De Atributos Físicos Do Solo Em Uma Sub-Bacia Às Margens Do Rio Mogi Guaçu (Sp)

Abstract: A espacialização dos atributos do solo é de grande importância na interpretação geográfica da paisagem especialmente quando o foco desejado são as questões hidrogeológicas acerca da capacidade de infiltração da água no solo, sendo a condutividade hidráulica seu indicador direto. Assim, este trabalho buscou verificar a existência de dependência espacial para as variáveis areia, argila, silte, densidade, micro e macro porosidade, volume total de poros e condutividade hidráulica, bem como analisar sua variabilida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Silt, clay, and sand content variabilities were classified as very high, medium, and low, respectively (53.35, 18.21, and 4.64% CV). These findings agree with those of Klinke, Oliveira and Pereira, (2017), who studied the physical properties of a Typic Haplustox (Oxisol) and obtained a very high variability for silt, medium for clay, and low for sand, with CVs of 52.03%; 17.37%; 6.18%, respectively. Thus, the granulometric attributes of the soil showed different variability, silt with very high variability, clay with medium variability, and sand with low variability, which indicates soil heterogeneity.…”
Section: Soil Propertiessupporting
confidence: 91%
“…Silt, clay, and sand content variabilities were classified as very high, medium, and low, respectively (53.35, 18.21, and 4.64% CV). These findings agree with those of Klinke, Oliveira and Pereira, (2017), who studied the physical properties of a Typic Haplustox (Oxisol) and obtained a very high variability for silt, medium for clay, and low for sand, with CVs of 52.03%; 17.37%; 6.18%, respectively. Thus, the granulometric attributes of the soil showed different variability, silt with very high variability, clay with medium variability, and sand with low variability, which indicates soil heterogeneity.…”
Section: Soil Propertiessupporting
confidence: 91%
“…This could be due to the textural variation and the consequent variation of the micro and macro porosity of the data, which were not measured and affected the result of the total porosity. Klinke Neto et al (2017) found a correlation of 0,53 the saturated hydraulic conductivity and macroporosity, being this the best result found among all attributes studied (texture, bulk density, total porosity, macroporosity and microporosity). Analyzing the spatial variability of the data, for the LVA soil class, the same authors found anisitropy only for the data of saturated hydraulic conductivity, macroporosity and total porosity.…”
Section: Resultsmentioning
confidence: 57%
“…Klinke Neto et al (2017) analyzed soil erosion processes in a subbasin of the MGEES and applied the USPED (unit stream power erosion and deposition) model. The sub‐basin presented 60% of the area with low taxes of erosion processes (due to low declivities) and sandy texture of soils (from eroded sediments of Group Itararé rocks), which are deep with high storage capacity and permeability, favouring groundwater recharge.…”
Section: Study Areamentioning
confidence: 99%